Physicochemical properties of absorbent hydrogel polymers in disposable baby diapers - Abd Manan, T.S.B. (Elsevier B.V., 2021)
Diapers are reusable waste. This research presents physicochemical properties of sodium polyacrylate in new (ND) and used (UD) diapers, via wavelength-dispersive X-ray fluorescence (WDXRF), Fourier transform infrared (FTIR), X-ray diffraction (XRD), pH, turbidity and colour. Additional constituents detected in ND, while others were slightly higher in UD. Slight decrease (2000â2500 cmâ1, UD) and bulk peaks (3287â3333 cmâ1, UD) were observed and functional group at 2897 cmâ1 (ND) disappeared showing their role as absorption sites. The pH (6.83â8.50), turbidity (16.3â36.6 NTU) and colour (153â432 Pt.Co) values were obtained. Thus, this provides a baseline reference for diapers application in concrete technology. Â© 2021 Elsevier B.V.